The evolution of planning thought in Serbia: Can planning be ‘resilient’ to the transitional challenges? - Peric, Ana (International Planning History Society Proceedings, 2016)
Planning is deeply embedded in a specific planning context: it implies not only planning system – institutional, legal and regulative framework of planning policies, but also planning culture – steering styles, norms, values, belief systems, visions and frames of the actors involved in the planning process. In recent decades the planning context changed as well in the western world as in developing countries. New approaches, instruments and tools have been developed and implemented. However, there is a great difference in the extent of implementation of innovative planning approach depending on a certain societal setting. Thus, it is a challenging task to observe the planning change throughout a transitional context. As evolutionary resilience is understood as seeking opportunities out of crises, the aim of this research is to identify the elements important for making the planning ‘resilient’ throughout transitional periods. To illustrate such an approach, the case study of Serbia – the state that has undergone the turbulent transformations in terms of its political, socio-economic and, consequently, planning system and practices, is chosen. Before proceeding with the overview of the planning system transformation in Serbia, a general framework made of factors affecting the evolution of planning thought are briefly presented: in addition to the mentioned systemic factors (laws, government, political and economic/market forces) and planning culture – the influence of local politics, local context and individuals or ‘movements’, will be shortly explained. Further, since the relationship between past, present and future is crucial to understand the nature of evolutionary process, the case study will be analysed through a brief historical overview of the planning evolution in Serbia, through: communist period (until 1989), post-communist phase (until 2000), and a contemporary period (until present). In order to achieve the analytical coherence, all the evolution stages will be observed through the lens of: context (prevailing ideology, state system), planning practice (and products of planning), and planning process (i.e. methodological approach). The contemporary planning modus in Serbia will be illustrated with a distinct example of the “Belgrade Waterfront” project, thus elucidating the contradictory interests and manifold influences of market, political, community and professional demands. The paper will end with highlighting the crucial factors for improving the ‘planning resilience’ within transitional systems, being these in the domains of stakeholder collaboration, position of planning expertise, or nature of governance arrangements.